Biogeochemical data of the 52nd Japanese Antarctic Research Expedition in austral summer of 2010-2011 - Iida, Takahiro; Odate, Tsuneo; Nishioka, Jun; Takamura, Tomomi; Fukuchi, Mitsuo (National Institute of Polar Research, 2012)
P(論文) departmental bulletin paper